Impact of India's publicly financed health insurance scheme on public sector district hospitals: a health financing perspective - Shankar Prinja; Maninder Pal Singh; Vipul Aggarwal; Kavitha Rajsekar; Praveen Gedam; Aarti Goyal; Pankaj Bahuguna (The Lancet Regional Health - Southeast Asia, 2023)
This paper evaluates the extent to which the PMJAY impacts the district hospitals from a financing perspective.
Keywords: Public health medicine